2007
DOI: 10.1126/science.1137603
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hepatic Stellate Cell Differentiation by the Neurotrophin Receptor p75 NTR

Abstract: Differentiation of hepatic stellate cells (HSCs) to extracellular matrix- and growth factor-producing cells supports liver regeneration through promotion of hepatocyte proliferation. We show that the neurotrophin receptor p75NTR, a tumor necrosis factor receptor superfamily member expressed in HSCs after fibrotic and cirrhotic liver injury in humans, is a regulator of liver repair. In mice, depletion of p75NTR exacerbated liver pathology and inhibited hepatocyte proliferation in vivo. p75NTR-/- HSCs failed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
144
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(156 citation statements)
references
References 26 publications
8
144
1
Order By: Relevance
“…42 A recent paper in Science highlighted the importance of activated HMs in hepatocyte proliferation. 43 The persistence and inflammatory/mitogenic phenotype of HMs inclusive of their expression of IL-6 and MMP9 depends on a high constitutive NF-B activity that is regulated at least in part by transcriptional repression of I B-␣ (mediated by CBF-1 and MeCP2) but also by IKK-dependent mechanisms under investigation in our laboratory. 44,45 Suppression of IKK activity in HMs with either a cell-permeable peptide that blocks the interaction of IKK␣/␤ with NEMO or by treatment with sulfasalazine (which inhibits IKK␣/␤) promotes Jun Nterminal kinase-dependent apoptosis.…”
Section: Nf-b As a Tumor Suppressor In Hepatocytesmentioning
confidence: 99%
“…42 A recent paper in Science highlighted the importance of activated HMs in hepatocyte proliferation. 43 The persistence and inflammatory/mitogenic phenotype of HMs inclusive of their expression of IL-6 and MMP9 depends on a high constitutive NF-B activity that is regulated at least in part by transcriptional repression of I B-␣ (mediated by CBF-1 and MeCP2) but also by IKK-dependent mechanisms under investigation in our laboratory. 44,45 Suppression of IKK activity in HMs with either a cell-permeable peptide that blocks the interaction of IKK␣/␤ with NEMO or by treatment with sulfasalazine (which inhibits IKK␣/␤) promotes Jun Nterminal kinase-dependent apoptosis.…”
Section: Nf-b As a Tumor Suppressor In Hepatocytesmentioning
confidence: 99%
“…9 Recent studies have shed light on the function of p75 neurotrophin receptor (p75NTR) in HSC activation and show that in p75NTRÀ/À mice, HSC are unable to become activated and to express aSMA. 10 Interestingly, p75NTR is effective in activating HSC in the absence of its ligand, nerve growth factor (NGF), signaling through activation of guanosine triphosphatase Rho. 10 Activation of members of Rho GTPase is reported to be crucial for HSC activation, as Rho inhibition attenuates liver fibrosis in several in vivo models.…”
mentioning
confidence: 99%
“…10 Interestingly, p75NTR is effective in activating HSC in the absence of its ligand, nerve growth factor (NGF), signaling through activation of guanosine triphosphatase Rho. 10 Activation of members of Rho GTPase is reported to be crucial for HSC activation, as Rho inhibition attenuates liver fibrosis in several in vivo models. 11,12 Quiescent HSC do not express p75NTR, but start expressing it on activation, 13 whereas hepatocytes do not express this receptor.…”
mentioning
confidence: 99%
“…p75NGFR has different functions based on the tumor type in which it is found. For example, it has been shown to exert a tumor-promoting effect in brain tumors and melanomas (11,12), whereas it has also been proposed as a potential tumor suppressor in bladder (7), stomach (9) and liver cancers (10). However, with the exception of a previous study reporting hypermethylation of p75NGFR in the serum of patients with colorectal cancer (13), no other studies to date have reported the methylation status, expression level, or function of p75NGFR in colorectal cancer.…”
Section: Introductionmentioning
confidence: 77%
“…The expression of p75NGFR has been observed in several human cancers, such as thyroid carcinoma, stomach cancer, and liver cancer (5)(6)(7)(8)(9)(10). p75NGFR has different functions based on the tumor type in which it is found.…”
Section: Introductionmentioning
confidence: 99%